Captcha as Graphical Password (International Journal of Engineering and Computer Science, 2018)
Security is the primitive issue in all the areas related to computers. Proper authentication is required to make the network secure. The traditional way of password using characters is vulnerable and easy to hack. So that method is integrated with new paradigms, such as Graphical Password, Captcha. Still the technology is evolving, a new security primitive based on hard AI problem, called Captcha as Graphical Password is evolving. CaRP is the combination of both Captcha and Graphical Password which make it hard to intruders to hack the password.